A nutrient-wide association study for risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition and the Netherlands Cohort Study - Papadimitriou, N; Muller, D; van den Brandt, PA; Perez-Cornago, A; Key, T; Et al. (Springer, 2019)
Purpose The evidence from the literature regarding the association of dietary factors and risk of prostate cancer is inconclusive.